Feeding behavior, intake pattern, and nutrient sufficiency of sheep fed sorghum straw silage and concentrate - Abdurrahman, Ahmad Mualif (2024)
This study aimed to determine the behavior, intake pattern, and nutritional sufficiency level of sheep fed sorghum straw silage and concentrate. Twelve male local sheep weighing 13.13 ± 2.39 kg were kept in individual pens with a size of 80 × 125 cm2. The concentrate comprised soybean meal, rice bran, ground corn, mineral premix, and urea. Forage and concentrate were given at the same time in different feed bunks and were available all the time. The data observed were related to behavior, feed intake, and growth. The behavioral activities observed were duration of eating, mineral block licking, drinking, rumination, laying, and other activities. The feed intakes observed were hourly intake and daily intake. Behavioral data and dry matter intake patterns were analyzed descriptively, while nutritional sufficiency was analyzed using a one-sample t test compared to the nutrient requirements of local sheep for an increase in body weight of 100 grams per day. The activities carried out within 24 hours were eating (24.00%), ruminating (19.05%), mineral block licking (3.45%), drinking (0.28%), laying (31.02%), and other activities (31.02%). The feed intake ratios of sorghum straw silage and concentrate were 10.89% and 89.11%, respectively, with an average daily gain of 140.00 g per head per day. The total dry matter intake was 737.34 g, consisting of a total intake of crude protein and total digestible nutrients of 16.48% and 71.44%, respectively, exceeding the needs of local sheep for a daily gain of 100 g per day. Sheep can use sorghum straw silage as a forage source and regulate their consumption to meet their nutritional needs.